Seabird bycatch in the Argentinean demersal longline fishery, 2001-2010 - Favero, Marco (2013)
Seabird mortality associated with fisheries is one of the major threats leading to population decreases of certain species, particularly albatrosses and petrels. The present study was conducted to (1) analyze seabird bycatch in the Argentinean demersal longline fishery during the decade 2001 to 2010, (2) provide a baseline of the levels of incidental mortality prior to the implementation of the National Plan of Action-Seabirds, and (3) characterize in space and time the occurrence and intensity of seabird mortality. Fishing effort decreased from some 30 million to 5 million hooks set per year, and the overall bycatch rate for the whole period was 0.033 (0.019 SE) birds per 1000 hooks. The estimated total mortality for the 10 yr period was 7470 ± 2449 seabirds, the majority being black-browed albatrosses and white-chinned petrels. Seabird mortalities decreased by 1 order of magnitude towards the end of the decade, not due to lower bycatch rates but to a drop in the number of hooks set per year. The progress achieved so far in Argentina is important, but if seabird bycatch is to be reduced to negligible levels, it is imperative that the National Plan of Action-Seabirds is effectively implemented and that the longline fishery comply with the conservation measure calling for the use of mitigation methods that came into effect in 2010. Other management-related actions, such as the increase of capacities within the National Observer Program and the refinement of seabird sampling protocols, will have an effect not only in the longline but also in the large trawl fishery, where seabird bycatch has also been documented.